Atividade antimicrobiana dos óleos essenciais de frutos verdes e maduros de Schinus terebinthifolius Raddi sobre isolados de Acinetobacter baumannii multirresistentes / Atividade antimicrobiana dos óleos essenciais de frutos verdes e maduros de Schinus terebinthifolius Raddi sobre isolados de Acinetobacter baumannii multirresistentes - Crisllany Tenório Costa Santos; Marcia Mayra Ramos de Azevedo; Chryslane Barbosa da Silva; Thiago José Matos Rocha; Aldenir Feitosa dos Santos; Luana Luzia Santos Pires (Universidade Estadual de Alagoas, 2019)
The increased resistance among isolates of Acinetobacter have been documented in various parts of the world, being responsible for cases of hospital infection outbreak, so the search for new bioactive compounds becomes relevant. From this, the work aimed to evaluate the antimicrobial activity of the essential oils of the unripe fruit of S. terebenthifolius and mature on isolates of A. baumannii. This essay was used the method of microdiluição in broth for the screening test and minimum inhibitory concentration (MIC). Pure essential oils (0.8 mL) 16% the emulsions were prepared with distilled water (4.2 mL) and Tween 80 (50 uL), which remained under constant stirring for 5 minutes in vortex. The volume (100uL) of oils to 16% were applied in triplicate wells with 100uL of Müeller-Hinton broth, ending with 10uL of bacterial suspension (5x106cfu/mL). For determination of the CIM, serial dilutions were made with 8% oils up 0.03125%. The essential oil of the fruit Green showed no antibacterial activity, while the essential oil of the low-hanging fruit was against up 0.03125%, which concludes that the essential oil of ripe fruits of mastic represents a new therapy against isolates of A. baumannii nosocomial infection involved in multidrug-resistant